The Use of English Film Media and Music to Improve Speaking Skill - Hanaya Deanita (English Instruction, 2020)
Speaking is one of the skills that must be mastered in English. The ability to speak in English is a person's skill in conveying his desires and thoughts to anyone orally. But in reality speaking is a language skill that has many obstacles that are often faced including mental, lack of ideas, embarrassment when speaking, fear of criticism, and many more. Therefore, the task of teachers in school is not only to convey material but also to try to motivate students to improve their language skills, especially speaking. In collecting the information, this study uses a literature review research method, namely by collecting some data that is in accordance with the problems to be discussed through previous research that has been published in online journals, both national and international journals. In learning a language, we must use appropriate and interesting techniques & media for learning so that students enjoy learning English. One of the media that can be used in the teaching and learning process is music and movies. By using the film, students will get to know new vocabulary and then they will record the new vocabulary in the film. Then they can speak in front of the class to retell the contents of the film briefly, convey the moral message contained in the film and explain the meaning of the moral message contained in the film.